SEROEPIDEMIOLOGICAL INVESTIGATION OF MYCOPLASMA BOVIS IN CALVES - Branka Vidić; Sara Savić; Živoslav Grgić; Ljiljana Suvajdžić; Nadežda Prica (Archives of Veterinary Medicine, 2015)
Within the multifactorial etiology of respiratory infections in cattle, Mycoplasmae play an important role. Most of the Mycoplasma microorganisms play a minor role in the development of the infections in cattle, contrary to Mycoplasma bovis (M. bovis) that is commonly the primary agent of the disease. Respiratory tract mucosa is the primary colonization site of M. bovis in cattle. Colonization of the upper respiratory tract of calves with M.bovis oft en occurs within the fi rst few weeks of life. Animals with chronic infection and without clinical symptoms occasionally shed M.bovis and they are highly important for the epidemiology of the infection. Stress factors such as transportation, entrance into the feeding object, coldness, etc. are associated with the secretion of M. bovis from a nose. Diagnostic procedure relies on clinical symptoms and detection of causative agent, regardless of whether the infection is found in individual animals or in the entire herd. Serological detection of M.bovis antibodies is often a reliable diagnostic method. The most used indirect method is ELISA test. During a two-year period, blood serum samples from calves (beef cattle) were examined and analyzed. Calves originated from cattle farms (big and small) of Holstein- Friesian and Simmental breed. The total number of 3777 samples was examined applying ELISA (Biovet Inc. Mycoplasma bovis Antibody Test Kit Bovichek® M.bovis). Positive fi ndings were obtained in 182 animals, i.e. 4.81%. Th e obtained results confi rmed the presence of M.bovis in cattle herds. Further research from epizootical aspect and the role of M.bovis in the occurrence of health problems in cattle population is necessary.